Understanding FDI Spillovers in the Presence of GVCs - Mercer-Blackman, Valerie; Xiang, Wei; Khan, Fahad (World Bank, Washington, DC, 2021)
Does a global value chain framework provide additional insights into the question of whether foreign direct investment is beneficial to host countries? The literature has found mixed results on whether foreign direct investment provides positive spillovers over and above mere financing. But the studies have focused on one country, or studies with an international focus tend to abstract from intersectoral linkages. By examining this question in the context of global value chains, this paper provides a much better understanding of the association as well as general validity. It harmonizes three major panel data sets: 1) the Multi-Regional Input-Output table for international input-output linkages, 2) the FDI Markets reports for greenfield foreign direct investment, and 3) the World Bank Enterprise Surveys for firm performance measures. The paper produces a rich panel data set from 2011 to 2017. The findings show that foreign direct investment has a positive effect on labor productivity in sectors and firms within those sectors. Moreover, global value chain participation plays a key role in shaping the foreign direct investment effects. Sectors with lower global value chain participation benefit more from foreign direct investment: doubling the foreign direct investment in those sectors results in an 8 percent productivity gain. The positive effect seems to be due to the increased competition created by foreign direct investment. Foreign direct investment spillovers also take place through domestic and foreign backward linkages, which means that foreign direct investment also has positive inter-sector and cross-border spillovers.